2018
DOI: 10.6061/clinics/2018/e480
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a novel mathematical model for the prediction of adult height and age at menarche in girls with idiopathic central precocious puberty

Abstract: OBJECTIVES:Unfavorable predicted adult height and psychosocial inadequacy represent parameters used to guide therapeutic intervention in girls with central precocious puberty. Gonadotropin-releasing hormone analog is the first-line treatment. The aim of this study was to compare two methods used to predict adult height and assess a validated tool for predicting the age at menarche in girls with central precocious puberty.METHODS:The predicted adult height of 48 girls with central precocious puberty was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Finally, another drawback of BA assessment is the absence of unanimity when choosing between average and advanced options in the Bayley–Pinneau height prediction table ( 29 ). In order to improve the prediction of adult height provided by BA assessment, several studies have suggested different predictive models in central precocious puberty ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, another drawback of BA assessment is the absence of unanimity when choosing between average and advanced options in the Bayley–Pinneau height prediction table ( 29 ). In order to improve the prediction of adult height provided by BA assessment, several studies have suggested different predictive models in central precocious puberty ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the prediction of adult height provided by BA assessment, several studies have suggested different predictive models in central precocious puberty (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Lopes et al [ 19 ] applied our mathematical model to 48 girls with idiopathic CPP. Their characteristics are similar to those of the 78 treated included in our model [ 7 ], except for their lower mean age at onset of puberty (5.75 vs 6.42 years) and greater interval time between the onset of puberty and treatment (2 vs 1.42 years).…”
Section: Discussionmentioning
confidence: 99%
“…By definition, height predictions are based on bone-age radiographs, which are highly imprecise and subject to substantial variability in interpretation. In addition, bone ages typically over-predict height in CPP [29]. Thus, it is very difficult to accurately predict height outcome for any individual child.…”
Section: Criteria For Treatmentmentioning
confidence: 99%